Magnetic properties and magnetic mineralogy of selected young volcanics from diﬀerent places of the Earth globe - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2009)
The  contemporary, historical and  recent volcanic  rocks were studied. An in- tention of the work  was to identify  a presence  of the so-called  low-temperature  oxidized titano-maghemite  (Ti-Mgh) phase  (if any)  in the young  volcanic  rocks.   In the  previous works it has been revealed  that this  phase  is a source  of the self-reversal  remanent mag- netization (RM)  in volcanic  rocks (Orlický, 2006,  2009;  Orlický and  Funaki, 2008).  The thermal demagnetization of the samples  and  inducing  of partial thermoremanent magne- tization (PTRM) of the samples  in the laboratory ﬁeld, the measurements of the change of magnetic susceptibility  (κ)  at selected  temperature  intervals of the compact samples and  the measurements of the Curie  temperatures and  the study  of behaviour of magnetic susceptibility (κ)  of samples  in the low and  high  temperature intervals were carried  out. In the macroscopically evidenced  oxidized basaltic scoria from the Tenerife  volcano a small portion of the low-temperature oxidized  Ti-Mgh  phase  was revealed.   A small  portion of the  low-temperature oxidized  phase  was  revealed  also  in  the andesite from  the  Rainier volcano  (20 000 years  old).  But a behaviour of magnetic susceptibility with  temperature, characteristic for a presence  of the low-temperature oxidized  Ti-Mgh  phase,  was revealed in older  basaltic scoria  of the Death Valley  (age  either  700 000 years  or more).  All other 12 laboratory investigated volcanic rocks have not possessed  the low-temperature oxidized Ti-Mgh  phase.